The progress in titanium alloys used as biomedical implants: From the view of reactive oxygen species - Yang, Jun; Liu, Chang; Sun, Hui; Liu, Ying; Liu, Zhaogang; Zhang, Dan; Zhao, Gang; Wang, Qiang; Yang, Donghong (Frontiers in Bioengineering and Biotechnology, 2022)
Due to superior mechanical properties and biocompatibility, medical titanium and titanium alloys are widely used in hard tissue replacement and orthodontic repair in orthopedic surgery and dentistry. In specific clinical populations such as the elderly, diabetics and patients with metabolic diseases, the failure rate of medical metal implants is increased significantly, putting them at increased risk of revision surgery. A large number of studies show that the content of reactive oxygen species (ROS) in the microenvironment of bone tissue surrounding implant materials is increased in patients undergoing revision surgery. And the accumulated ROS break the original balance of oxidation and anti-oxidation, resulting in host oxidative stress damage. However, the addition of active elements to medical titanium and titanium alloys can be used as antibacterial agents, which can greatly reduce the risk of postoperative infection in patients. The metal oxide nanoparticles of active elements have strong antimicrobial properties. The oxides acting as antimicrobial agents can be divided into two major groups based on their mechanism of action i.e., those that involve oxidation and those that inhibit the production of ROS. In addition, as a strong oxidant, ROS cause electrochemical corrosion in vivo and consequent degradation of implant materials, leading to the loosening of implant materials, which tends to affect their long-term stability. Therefore, ROS may act as a messenger substance for the communication between the host and the implanted material, which run through the entire wound repair process and play a role that cannot be ignored. This paper reviews the interaction between oxidative stress and materials is reviewed, the generation and development of oxidative stress products during implantation of implant materials. Furthermore, this review introduces the effects of oxidative stress products on osseointegration and implant life. This facilitates the development of a new generation of well-biocompatible implant materials with ROS responsiveness, and ultimately prolong the lifespan of implants.